Expectations of audit employers. - Chew, Soo Shyan. (2008)
This study focuses on the changing expectations of local audit employers in the Knowledge-Based Economy. The objectives of our study are to determine the competencies required of NTU BAcc graduates, and if there is any difference in the Big 5 and the local CPA firms' perceptions about the desired competencies for entry level graduate auditors.